Problematic mobile phone use and big-five personality domains - Motoharu Takao (Wolters Kluwer Medknow Publications, 2014)
Background: Although a mobile phone is useful and attractive as a tool for communication and interpersonal interaction, there exists the risk of its problematic or addictive use. Objectives: This study aims to investigate the correlation between the big-five personality domains and problematic mobile phone use. Materials and Methods: The Mobile Phone Problem Usage Scale and the NEO Five-Factor Inventory (NEO-FFI) were employed in this study. Survey data were gathered from 504 university students for multiple regression analysis. Results: Problematic mobile phone use is a function of gender, extraversion, neuroticism, openness-to-experience; however, it is not a function of agreeableness or conscientiousness. Conclusions: The measurement of these predictors would enable the screening of and intervening in the potentially problematic behaviors of mobile phone users.